Specific Aspects and Advantages of the Process of Distance Learning in Teaching Foreign Languages - Sharofat Begasheva Nematullayevna (Genius Publishing Group, 2022)
This article discusses the specifics and advantages of distance learning in foreign language teaching. Another advantage of distance learning is that the student can study at a convenient time and even without leaving work. It is because of these advantages that this style is becoming more and more popular in the world
Keywords: Linguistics; Foreign Language; Distance Learning; Education